Effects of Blast Loading on Prestressed Girder Bridges - William F. Cofer; Debra S. Matthews; David I. McLean (Shock and Vibration)
Since the events of September 11th, increased attention has been given to the effects of blast loading on structures. Bridges are especially important due to their potentially critical role in the economy and for emergency response. Prestressed concrete highway bridges are very common, representing 11 percent of state bridges nationwide. Yet, very little is known about how prestressed concrete bridges respond to blast loading.